CA STATE FIREMENS ASSN - STEIMER,HF (Tufts Archival Research Center, 2007)
Marginalia; Letter from the California State Firemen's Association Inc. to all Congressmen and Senators of California urging them to vote for the Boucher/Bliley bill "Fire Safe Cigarette Act of 1989". Points to the fact that this bill is based on the research of a study done by a panel put together by firemen's associations and the tobacco industry.